REVIEW: MEDICINAL PLANTS WITH PHARMACOLOGICAL ACTIVITY AS ANTIPYRETIC - Nurdiani Adiningsih; Dika Pramita Destiani (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
Fever is a medical condition characterized by an increased body temperature beyond the normal range of 36 â€“ 37Â°C. If not managed appropriately, fever may lead to complications in therapy. The conventional treatment for fever involves using antipyretics such as paracetamol/acetaminophen, and ibuprofen. However, prolonged use of these synthetic medications may have adverse side effects. Consequently, more patients are turning to herbal medicine to manage fever. This review aims to identify medicinal plants with pharmacological activity as antipyretics. We conducted a systematic literature review using Google Scholar as the search engine database. Our search keywords were â€œtanaman herbalâ€, â€œantipiretik", â€œpenurun demam", and "uji aktivitas antipiretik". In this review, a total of 18 articles were meticulously analyzed. The collective findings from these studies demonstrated that all tested medicinal plants exhibited antipyretic activity. Flavonoids, tannins, and terpenoids were the primary constituents responsible for the observed antipyretic activity. Medicinal plants with alkaloids and steroid content were also believed to exhibit antipyretic activity. Keywords: fever, antipyretics, medicinal plants